Some Notes to the Language of Two Late Byzantine Poems - Juan José, Pomer Monferrer (Universidad Nacional de La Plata. Facultad de Humanidades y Ciencias de la Educación. Centro de Estudios Helénicos, 2019)
The Byzantine poems entitled Î£Ï…Î½Î±Î¾á½±Ï Î¹Î¿Î½ Ï„Î¿á¿¦ Ï„Î¹Î¼Î·Î¼á½³Î½Î¿Ï… Î³Î±Î´á½±Ï Î¿Ï… and Î“Î±Î´á½±Ï Î¿Ï…, Î»á½»ÎºÎ¿Ï… ÎºÎ¹ á¼€Î»Î¿Ï…Ï€Î¿á½ºÏ‚ Î´Î¹á½µÎ³Î·ÏƒÎ¹Ï‚ á½¡Ï Î±á½·Î± offer a significant and clear example about the interaction between two opposite linguistic registers: from the one hand, the literary Greek used for poetic composition; from the other, the popular Greek which was gradually gaining ground in order to substitute the old language.